Relationships between surrogate measures of mechanical and psychophysiological load, patellar tendon adaptations, and neuromuscular performance in NCAA division I men's volleyball athletes - Guthrie, B. M.; King, E. L.; Patwardhan, S.; Wei, Q.; Sikdar, S.; Chitnis, P. V.; Jones, M. T. (Frontiers in Sports and Active Living, 2023)
Introduction: Patellar tendon adaptations occur in response to mechanical load. Appropriate loading is necessary to elicit positive adaptations with increased risk of injury and decreased performance likely if loading exceeds the capacity of the tendon. The aim of the current study was to examine intra-individual associations between workloads and patellar tendon properties and neuromuscular performance in collegiate volleyball athletes.